2008
DOI: 10.1175/2007jas2378.1
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Generalization of Singular Vectors: Behavior in a Baroclinic Unstable Flow

Abstract: Singular vector (SV) analysis has proved to be helpful in understanding the linear instability properties of various types of flows. SVs are the perturbations with the largest amplification rate over a given time interval when linearizing the equations of a model along a particular solution. However, the linear approximation necessary to derive SVs has strong limitations and does not take into account several mechanisms present during the nonlinear development (such as wave-mean flow interactions). A new techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 46 publications
(51 reference statements)
0
30
0
Order By: Relevance
“…Considering that the linearity of SVs does not take into account some mechanisms presented during the nonlinear development (such as wave-mean flow interactions), Riviere et al [26] applied a CNOP-like approach, a modified version of nonlinear singular vector (NLSV) approach developed by Mu [17] , in a two-layer quasigeostrophic model to investigate the effect of nonlinearities on the behavior of baroclinic unstable flows. In that study, the authors defined the objective function related to the so-called NLSV with perturbation growth rate, and confined the initial perturbations on the boundary of a constraint.…”
Section: Nonlinear Behavior Of Baroclinic Unstable Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the linearity of SVs does not take into account some mechanisms presented during the nonlinear development (such as wave-mean flow interactions), Riviere et al [26] applied a CNOP-like approach, a modified version of nonlinear singular vector (NLSV) approach developed by Mu [17] , in a two-layer quasigeostrophic model to investigate the effect of nonlinearities on the behavior of baroclinic unstable flows. In that study, the authors defined the objective function related to the so-called NLSV with perturbation growth rate, and confined the initial perturbations on the boundary of a constraint.…”
Section: Nonlinear Behavior Of Baroclinic Unstable Flowsmentioning
confidence: 99%
“…For example, Liu [25] proved theoretically that CNOPs locate at the boundary of a given constraint, which coincides with the numerical results demonstrated by other papers [5,18] . Riviere et al [26] applied CNOP-like approach in a two-layer quasi-geostrophic model of baroclinic instability to investigate the effect of nonlinearities on the behavior of baroclinic unstable flows. Terwisscha van Scheltinga [27] computed the CNOPs of the double-gyre ocean circulation by an implicit 4D-Var methodology and studied the finite amplitude stability of the double-gyre flow.…”
mentioning
confidence: 99%
“…The CNOP method represents an extension of the linear SV method to nonlinear regimes (Mu and Duan, 2003). It has been used for studying several pertinent areas: ENSO predictability (Duan and Mu, 2006;Mu et al, 2007b;Yu et al, 2009;Duan and Zhang, 2010), the sensitivity and passive variability of the ocean thermohaline circulation (THC) (Mu et al, 2004;Sun et al, 2005), double-gyre ocean circulations (Terwisscha van Scheltinga and Dijkstra, 2008), the nonlinear behavior of baroclinically unstable flows (Rivier et al, 2008), and ensemble forecasting (Mu and Jiang, 2008). In the study of Mu et al (2007aMu et al ( , 2009 for targeted observations, they found that the forecasts benefit more from reductions of CNOP-type initial errors than from reductions of SV-type initial errors.…”
Section: Introductionmentioning
confidence: 99%
“…The former has been largely investigated, and many theories and methods have been proposed or introduced (Lorenz, 1965;Toth and Kalnay, 1997;Mu et al, 2003;Mu and Zhang, 2006;Riviere et al, 2008), in which optimal methods are important for estimating the limit of the predictability of weather and climate events. The application of a singular vector (SV; Lorenz, 1965;Farell, 1989) in meteorology is pioneer in this scenario.…”
Section: Introductionmentioning
confidence: 99%